Does movie violence incrase violent crime? - Dahl, Gordon B. 1968-; Della Vigna, Stefano 1973- (National Bureau of Economic Research, 2008)
Laboratory experiments in psychology find that media violence increases aggression in the short run. We analyze whether media violence affects violent crime in the field. We exploit variation in the violence of blockbuster movies from 1995 to 2004, and study the effect on same-day assaults. We find that violent crime decreases on days with larger theater audiences for violent movies. The effect is partly due to voluntary incapacitation: between 6PM and 12AM, a one million increase in the audience for violent movies reduces violent crime by 1.1 to 1.3 percent. After exposure to the movie, between 12AM and 6AM, violent crime is reduced by an even larger percent. This finding is explained by the self-selection of violent individuals into violent movie attendance, leading to a substitution away from more volatile activities. In particular, movie attendance appears to reduce alcohol consumption. Like the laboratory experiments, we find indirect evidence that movie violence increases violent crime; however, this effect is dominated by the reduction in crime induced by a substitution away from more dangerous activities. Overall, our estimates suggest that in the short-run violent movies deter almost 1,000 assaults on an average weekend. While our design does not allow us to estimate long-run effects, we find no evidence of medium-run effects up to three weeks after initial exposure.